INFLUENCE OF DIVERSIFICATION STRATEGIES ON COMPETITIVE ADVANTAGE OF COMMERCIAL BANKS IN KENYA - Wanjiru, Karani Winnie; Nzulwa, Dr. Joyce (Journal of Business and Strategic Management, 2018)
Purpose: This study examined the influence of diversification strategies on competitive advantage of commercial banks in Kenya by utilizing theoretical approaches of Market Power Theory, Portfolio Theory, Transaction Cost Theory, Resource Based View Theory and Diffusion of Innovation Theory. The specific objectives of the study included: to establish the influence of asset diversification strategy, technological diversification strategy, portfolio diversification strategy and revenue diversification strategy on competitive advantage of commercial banks in Kenya. Methodology: The stud adopted a descriptive research design. The target population of the study comprised of all the 43 commercial banks in Kenya. However, the study focused on the 39 commercial banks which were operational at the time of the study. The target respondents were the director of the corporate section, the head of strategy department and the strategy manager from each of the 39 commercial banks who made a total of 117 respondents. The study used a census method on all the 39 commercial banks. The study mainly relied on primary data. The primary data was collected using questionnaires which comprised open and closed- ended questions. Data was quantitatively analyzed using (SPSS V20) for both descriptive and inferential statistics. Results: The study findings showed that all the four variables, that is asset diversification strategy, technological diversification strategy, portfolio diversification strategy and revenue diversification strategy have a positive and significant influence on competitive advantage of commercial banks in Kenya. Recommendations: The study recommends that commercial banks should aim to increase their asset diversification strategies. The study also recommends that commercial banks should also aim to increase their technological diversification strategies. The study also recommends that commercial banks should also invest more resources in expanding their revenue generation activities. The study finally recommends that commercial banks should also invest more resources in expanding their portfolios as to diversify their risks.